2010
DOI: 10.1021/pr100529t
|View full text |Cite
|
Sign up to set email alerts
|

Secretome-Based Identification and Characterization of Potential Biomarkers in Thyroid Cancer

Abstract: In search of thyroid cancer biomarkers, proteins secreted by thyroid cancer cell lines, papillary-derived TPC-1 and anaplastic-derived CAL62, were analyzed using liquid chromatography-tandem mass spectrometry. Of 46 high-confidence identifications, 6 proteins were considered for verification in thyroid cancer patients' tissue and blood. The localization of two proteins, nucleolin and prothymosin-α (PTMA), was confirmed in TPC-1 and CAL62 cells by confocal microscopy and immunohistochemically in xenografts of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 73 publications
2
27
0
2
Order By: Relevance
“…Cancer cell diVerentiation [50,66] Upper urinary tract Protein in tissue Tumor recurrence [59] recorded in bladder tumors compared with their normal adjacent tissues, which was most prominent in tumors of a higher grade. In upper urinary tract cancer, tumor recurrence was associated with proT overexpression, but only when the polypeptide was localized in the tumor-cell cytoplasm [59].…”
Section: The Dual-intracellular and Extracellular-role Of Protmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cell diVerentiation [50,66] Upper urinary tract Protein in tissue Tumor recurrence [59] recorded in bladder tumors compared with their normal adjacent tissues, which was most prominent in tumors of a higher grade. In upper urinary tract cancer, tumor recurrence was associated with proT overexpression, but only when the polypeptide was localized in the tumor-cell cytoplasm [59].…”
Section: The Dual-intracellular and Extracellular-role Of Protmentioning
confidence: 99%
“…Indeed, soon after its identiWcation, proT was detected in human blood [64], its presence attributed either to leakage from damaged leukocytes or "secretion" from proT -rich cells via an as yet unknown mechanism. Nevertheless, to date, proT detection in cancer patients' sera is reported in only two studies (a) in breast cancer patients [65] and (b) in a secretome analysis of thyroid carcinomas [66]. Unfortunately, no correlation of blood proT levels with cancer development and/or prognosis was found.…”
Section: The Dual-intracellular and Extracellular-role Of Protmentioning
confidence: 99%
“…1,35 Remarkably, accumulating evidence suggests that ENO1 can function as an oncogenic protein by promoting cell proliferation, invasion and metastasis. ENO1 expression is frequently increased in diverse tumors, including head and neck, 6 thyroid, 7 breast, 8 lung, 9,10 prostate, 11 colon and gastric cancer, 12,13 glioma 14 and cholangiocarcinoma. 15 Moreover, overexpression of ENO1 is positively associated with progression and poor prognosis in several tumors.…”
mentioning
confidence: 99%
“…Remarkably, accumulating evidence have suggested that ENO1 can function as an oncogenic protein by promoting cell proliferation, invasion and metastasis. ENO1 expression is frequently increased in diverse tumors, including head and neck, thyroid, breast, lung, prostate, colon and gastric cancer, glioma and cholangio carcinoma (46)(47)(48)(49). Moreover, overexpression of ENO1 is positively associated with progression and poor prognosis in several tumors (49).…”
Section: Discussionmentioning
confidence: 99%